Was könnte Grundtvig heutzutage für reformierte Christen bedeuten? - Herngreen, G. F. W. (Grundtvig-studier, 1976)
What might Grundtvig mean today to Reformed Christiansf By G. F. W. Herngreen The author, a former vicar in the Hague, asks this question on the basis of his knowledge of both Grundtvig’s writings and of the Grundtvigian church life in Denmark. Two of Grundtvig’s hymns have recently been included in the Dutch Hymn Book (Liedboek) and in this connection Grundtvig’s theology has for the first time received close consideration. In this article the author discusses in depth his view of the relationship between the Calvinist and the Grundtvigian interpretation of the Eucharist, particularly with regard to Karl Barth’s theology, and finds a greater agreement than even Grundtvig himself was aware of. The Reformed teaching on the Eucharist offers a greater opportunity to understand Grundtvig’s deepest concern: where do we hear God’s word to us personally? Grundtvig’s reference to the congregation’s ‘loud yes and amen’ in the creed during baptism is in consonance with Calvin’s main concern that man has no control over God’s word, not even at the Eucharist.It is God, the free agent, who acts through His word at both sacraments - not man. The creed is not a number of dogmas, a different holy writ from the Bible, but an oral narrative about who God is. This interpretation may lead to a cult-fellowship with its back to the world, which is at variance with the Reformed view that the true service takes place in the everyday life of the world, but it is for this very reason of great importance for the ecumenical debate whether one can also explain to the Reformed churches the basic idea behind Grundtvig’s ‘ First a man, then a Christian’.